2020
DOI: 10.3390/met10081027
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Al-Mg-Si Wire Rod Heat Treatment on Its Electrical Conductivity and Strength

Abstract: The raw material for the production of Al-Mg-Si wires is wire rods, created in the Continuus Properzi line in temper T1 (cooled after forming at an elevated temperature and after natural aging). The general technologies for shaping the mechanical and electrical properties of Al-Mg-Si wire rods include two kinds: high- and low-temperature heat treatments. High-temperature heat treatment includes a homogenization process and a supersaturation process. Low-temperature heat treatment takes place after supersaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Smyrak et al [ 61 ] also studied two alloys with different levels of Mg and Si while having the same Mg/Si ratio (~ 1): Al-0.72 Mg-0.71Si (HA) and Al-0.56 Mg-0.56Si (LA). The alloys were subjected to a solution treatment for 12 h at 550 °C, followed by natural aging for 24 h and then artificial aging at different temperatures (from 100 to 240 °C) and various time intervals (0-24 h); the associated results are displayed in Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Smyrak et al [ 61 ] also studied two alloys with different levels of Mg and Si while having the same Mg/Si ratio (~ 1): Al-0.72 Mg-0.71Si (HA) and Al-0.56 Mg-0.56Si (LA). The alloys were subjected to a solution treatment for 12 h at 550 °C, followed by natural aging for 24 h and then artificial aging at different temperatures (from 100 to 240 °C) and various time intervals (0-24 h); the associated results are displayed in Fig.…”
Section: Figurementioning
confidence: 99%
“…However, the HA alloy exhibited a higher strength at the high resistivity end relative to the LA alloy, presumably owing to a larger density number of precipitates in the HA alloy. It was reported that the optimal strength and EC (200 MPa-57.5% IACS) were acquired at 150 °C within 4-10 h for both alloys, which are favorable for the subsequent wire drawing to produce wires with high strength and high EC [ 61 ]. Reprinted with permission from [ 61 ].…”
Section: Figurementioning
confidence: 99%
“…a) ACSR and b) AAACs. [ 7 ] This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license ( http://creativecommons.org/licenses/by/4.0/).…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion of fine fractions, such as metal chip, dusts, powders, tapes, etc., allows an effective plastic consolidation and the obtaining of a coherent material which has good utility properties [9][10][11][12][13][14][15]. Consolidation of the 6082 alloy chips by pressing and extrusion makes it possible to obtain briquettes with better fatigue properties compared to the solid material [16][17][18]. One of the materials most often used in the industry is aluminum and its alloys, in particular, alloy 6082.…”
Section: Introductionmentioning
confidence: 99%